Optimising the management of childhood acute diarrhoeal disease using a rapid test-and- treat strategy and/or Lactobacillus reuteri DSM 17938: a multicentre, randomised, controlled, factorial trial in Botswana. Issue 4 (13th April 2022) - Pernica, Jeffrey M; Arscott-Mills, Tonya; Steenhoff, Andrew P; Mokomane, Margaret; Moorad, Banno; Bapabi, Mbabi; Lechiile, Kwana; Mangwegape, Oarabile; Batisani, Boswa; Mawoko, Norah; Muthoga, Charles; Vanniyasingam, Thuvaraha; et al.
Abstract : Introduction: The study aim was to determine if rapid enteric diagnostics followed by the provision of targeted antibiotic therapy ('test-and-treat') and/or Lactobacillus reuteri DSM 17938 would improve outcomes in children hospitalised in Botswana with acute gastroenteritis. Methods: This was a multicentre, randomised, factorial, controlled, trial. Children aged 2–60 months admitted for acute non-bloody diarrhoea to four hospitals in southern Botswana were eligible. Participants were assigned to treatment groups by web-based block randomisation. Test-and-treat results were not blinded, but participants and research staff were blinded to L. reuteri /placebo assignment; this was dosed as 1×10 8 cfu/mL by mouth daily and continued for 60 days. The primary outcome was 60-day age-standardised height (HAZ) adjusted for baseline HAZ. All analyses were by intention to treat. The trial was registered at Clinicaltrials.gov. Results: Recruitment began on 12 June 2016 and continued until 24 October 2018. There were 66 participants randomised to the test-and-treat plus L. reuteri group, 68 randomised to the test-and-treat plus placebo group, 69 to the standard care plus L. reuteri group and 69 to the standard care plus placebo group. There was no demonstrable impact of the test-and-treat intervention (mean increase of 0.01 SD, 95% CI −0.14 to 0.16 SD) or the L. reuteri intervention (mean decrease of 0.07 SD, 95% CI −0.22 to 0.08 SD) on adjusted HAZ at 60 days. Conclusions: In children hospitalised for acute gastroenteritis in Botswana, neither a test-and-treat algorithm targeting enteropathogens, nor a 60-day course of L. reuteri DSM 17938, were found to markedly impact linear growth or other important outcomes. We cannot exclude the possibility that test-and-treat will improve the care of children with significant enteropathogens (such as Shigella ) in their stool. Trial registration number: NCT02803827 .